Pelatihan Penulisan Karya Jurnalistik dan Menjadi Presenter Berita Handal di SMA Budi Agung Medan - Suryanto Suryanto; Dani Manesah; Silvia Lestari; Athaya Khairani Ningtyas; M. Fariz Rizantha (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2025)
This training aims to enhance the skills of students at SMA Budi Agung Medan in journalistic writing and becoming skilled news presenters. The method employed includes a participatory approach through intensive training, group discussions, and hands-on practice. The program provides an in-depth understanding of journalistic writing techniques, mastery of news language, as well as confidence and techniques for on-camera presentations. The training results show a significant improvement in participants' abilities, both in writing news articles according to journalistic standards and delivering news professionally. This training has a positive impact on students' communication skills while preparing them to face the challenges of the mass media industry.